Biomechanical design of Less Invasive Stabilization System femoral plates: Computational evaluation of the fracture environment. (October 2014) - Reina-Romo, Esther; Giráldez-Sánchez, MA; Mora-Macías, J; Cano-Luis, P; Domínguez, Jaime
Less Invasive Stabilization System femoral plates are currently accepted as a suitable fixation technique for supra-intercondylar femoral fractures. However, general agreement does not exist regarding the optimum design of this fixator type. Therefore, the aim of this article is to reduce the intrinsic Less Invasive Stabilization System complications by clarifying, from a biomechanical point of view, how the number of screws, the screw connection type (unicortical or bicortical), or the structured position of the screws can influence the outcome of the fracture site. These studies include a specific finite element analysis that determines how several biomechanical variables, such as the movement at the fracture site, are influenced by the preconditions of bone healing. The results of this study show that the screw type affects the mechanical stabilization of the femur to a greater extent than the material type of the Less Invasive Stabilization System femoral plates. The most significant differences among all the analyzed configurations are observed in the shear interfragmentary strain between screw types. Values are approximately 50% higher with unicortical screws than with bicortical ones.